HCI in business : second International Conference, HCIB 2015, held as part of HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings /: second International Conference, HCIB 2015, held as part of HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings. (2015) - Unknown
No abstract available